Causes of a Block to Forearm Rotation after Distal Radius Fractures - Mok, Daniel; Chidambaram, Ramiah; Nakamura, Toshiyasu (Journal of Wrist Surgery, 2013)
Three cases of a block to forearm rotation after a distal radius fracture were presented. The unique feature is that the surgeon should be diligent in seeking and rectifying causes of distal radioulnar joint (DRUJ) instability and rotation loss after fracture treatment.
Keywords: distal radius fracture; DRUJ; TFCC; ulnar styloid fracture; volar locking plate